2006
DOI: 10.1128/jvi.80.3.1231-1241.2006
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the Yeast yTHC Collection Identifies Essential Host Factors Affecting Tombusvirus RNA Recombination

Abstract: RNA recombination is a major process in promoting rapid virus evolution in an infected host. A previous genome-wide screen with the yeast single-gene deletion library of 4,848 strains, representing ϳ80% of all genes of yeast, led to the identification of 11 host genes affecting RNA recombination in Tomato bushy stunt virus (TBSV), a small model plant virus (E. Serviene, N. Shapka, C. P. Cheng, T. Panavas, B. Phuangrat, J. Baker, and P. D. Nagy, Proc. Natl. Acad. Sci. USA 102:10545-10550, 2005). To further test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 66 publications
1
106
0
1
Order By: Relevance
“…Screening the recombination efficiency of TBSV using a yeast single-knockout library revealed that host genes involved in RNA degradation were suppressing the generation of new viral RNA recombinants. In contrast, genes contributing to the intracellular transport of proteins were identified as viral RNA recombination accelerators (Serviene et al, 2005;Serviene et al, 2006). In this study, approximately one quarter of the CfMV and RGMoV genomes were monitored with highly sensitive and specific RT-PCR for the generation of recombinant molecules in co-inoculated oat plants.…”
Section: Discussionmentioning
confidence: 99%
“…Screening the recombination efficiency of TBSV using a yeast single-knockout library revealed that host genes involved in RNA degradation were suppressing the generation of new viral RNA recombinants. In contrast, genes contributing to the intracellular transport of proteins were identified as viral RNA recombination accelerators (Serviene et al, 2005;Serviene et al, 2006). In this study, approximately one quarter of the CfMV and RGMoV genomes were monitored with highly sensitive and specific RT-PCR for the generation of recombinant molecules in co-inoculated oat plants.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their limited genetic complement, viruses need to recruit numerous host factors to be able to replicate and move inside the infected plant. This is exemplified by genome-wide screens performed in yeast, in which over 100 genes with diverse functions and involved in a variety of cellular processes turned out to have an effect on the replication and recombination of Tomato bushy stunt virus (TBSV; Panavas et al, 2005;Serviene et al, 2005Serviene et al, , 2006. TBSV belongs to the Tombusviridae family, whose members, like potyviruses, contain linear single-stranded (+) RNA genomes.…”
Section: Dip2-mediated Enhanced Potyvirus Resistance Is Independent Omentioning
confidence: 99%
“…Tomato bushy stunt virus recombination in a model host, yeast Saccharomyces cerevisiae, is enhanced 10-to 50-fold in host XRN1 5-39 exoribonuclease-negative mutant cells (Serviene et al 2006). Various housekeeping RNases that are abundantly distributed in intracellular compartments such as lysosomes, endoplastic reticulum, and ribosomes also could potentially act on the 39 termini of viral RNAs (Irie 1999).…”
Section: Introductionmentioning
confidence: 99%